Current legal problems - Lloyd Lord (editor); Rideout Roger (editor); Venables Robert (editor) (London : Stevens & Sons, 1975)
The Current Legal Problems (CLP) annual volume is published on behalf of University College London, Faculty of Laws. It is based on the Faculty's annual lecture series that was established over sixty years ago. The lectures are public, delivered on a weekly basis and chaired by members of the judiciary. CLP features scholarly articles that offer a critical analysis of important current legal issues. It covers all areas of legal scholarship and features a wide range of methodological approaches to law. With its emphasis on contemporary developments, CLP is a major point of reference for legal scholarship
Includes index p.249 - 252.
eng.
Keywords: Judicial review -- Great Britain; Judicial activism; Source of Soviet law